Komposisi dan Kandungan Kolesterol Karkas Ayam Broiler Diare yang Diberi Tepung Daun Salam (Syzygium polyanthum Wight) dalam Ransum - S Suharti; A Banowati; W Hermana; K G Wiryawan (Media Peternakan, 2008)
Diarrhea is one of diseases in broiler chicken. Antibiotics are usually used to cure the disease. However, there are many risks caused by the use of antibiotic in poultry industries for human health. The risks are carcinogenic effect and resistance to the antibiotics. Therefore the use of antibiotics needs to be replaced by natural antimicrobes. One of the natural antimicrobes is bay leaves which contains volatile oils, tannins and flavonoids. This research was conducted to study the effect of bay leaves powder addition in the ration on the body weight, carcass percentage, carcass commercial cut and carcass cholesterol of the broiler using completely randomized design with six treatments and three replications. The research used 180 DOC (Day Old Chicken). The treatment diets were: R0 (control), R1 (control with infected Eschericia coli), R2 (1% bay leaves powder), R3 (2% bay leaves powder), R4 (3% bay leaves powder), R5 (antibiotic). The data were analyzed using analyses of variance and any significant difference was further tested by Duncan test. The results showed that the treatment diets did not significantly increase body weight, carcass percentage, and carcass commercial cut percentage. The treatment significantly decreased carcass cholesterol level. It is concluded that bay leaves meal could replaced the use of antibiotic in broiler ration and reduced carcass cholesterol. Key words: bay leave, E. coli, body weight, carcass, cholesterol